Prevalence survey of healthcare-associated infections and antimicrobial use at the University Hospital "Paolo Giaccone", Palermo, Italy - Sinatra, I; Carubia, L; Marchese, V; Aprea, L; D'Alessandro, N; Mammina, C; Torregrossa, M V (Journal of preventive medicine and hygiene, 2013)
Healthcare-associated infections (HAIs) and antimicrobial resistance are well known major public health threats. The first goal of our study was to describe the prevalence of HAI, while the second goal was to describe the antibiotic consumption at our University Hospital, "P. Giaccone" in Palermo, Italy. A standardized methodology for a combined Point Prevalence Survey (PPS) on healthcare-associated infections (HAIs) and antimicrobial use in European acute care hospital developed by the European Centre for Disease Prevention and Control (ECDC) was piloted across Europe. The teaching Hospital "P. Giaccone" in Palermo, Italy, participated in the study. Out of 328 surveyed patients, 12 (3.6%) had an HAI and 159 (48.5%) were receiving at least one antimicrobial agent. Prevalence results were highest in intensive care units, with 17.6% patients with HAI. Bloodstream infections represented the most common type (50%) of HAI. Surgical prophylaxis was the indication for antimicrobial prescribing in 59 (37.1%) out of 159 patients and exceeded 24 hours in 54 (91.5%) cases. The results suggest that in our hospital there was a frequent and inappropriate use of antimicrobials, especially in the setting of surgical prophylaxis.